The Role of Organizational Learning on Employee Performance through Motivation and Organizational Commitment as Mediation Variables - Faradhita Fitriana Nurul Fajri; Suhana Suhana (Universitas Pamulang, 2022)
This study aims to determine the mediating role of motivation and organizational commitment on organizational learning on employee performance with a study on employees of PT Astra International Tbk Yogyakarta Branch. The sample of this study were all employees of PT Astra International Tbk Yogyakarta Branch, with the sampling technique was saturated sampling. The analysis technique used statistical analysis consisted of descriptive analysis, Structural Equation Modeling (SEM), Conformity Test and Statistical Test, Hypothesis Testing. The results of this study organizational learning has a positive effect on work motivation, organizational learning has a positive effect on organizational commitment, work motivation has a positive effect on organizational commitment, organizational learning has a positive effect on employee performance, work motivation has a positive effect on employee performance, and organizational commitment has a positive effect on performance. employee.